Foreign workers in Singapore : integrating or segregating them? - Chin, Yolanda (2009)
The recent saga over the housing of foreign workers in land-scarce Singapore has polarized Singaporeans into two camps - those calling for integration and those for segregation. Although integration is possibly the more morally defensible of the two doctrines, it is segregation that is likely to prevail in practice.